FORUM: Sustaining ecosystem functions in a changing world: a call for an integrated approach. Issue 5 (25th June 2013) - Tomimatsu, Hiroshi; Sasaki, Takehiro; Kurokawa, Hiroko; Bridle, Jon R.; Fontaine, Colin; Kitano, Jun; Stouffer, Daniel B.; Vellend, Mark; Bezemer, T. Martijn; Fukami, Tadashi; Hadly, Elizabeth A.; van der, Marcel G.A.; et al.
Summary With ever‐increasing human pressure on ecosystems, it is critically important to predict how ecosystem functions will respond to such human‐induced perturbations. We define perturbations as either changes to abiotic environment (e.g. eutrophication, climate change) that indirectly affects biota, or direct changes to biota (e.g. species introductions). While two lines of research in ecology, biodiversity–ecosystem function (BDEF) and ecological resilience (ER) research, have addressed this issue, both fields of research have nontrivial shortcomings in their abilities to address a wide range of realistic scenarios. We outline how an integrated research framework may foster a deeper understanding of the functional consequences of perturbations via simultaneous application of (i) process‐based mechanistic predictions using trait‐based approaches and (ii) detection of empirical patterns of functional changes along real perturbation gradients. In this context, the complexities of ecological interactions and evolutionary perspectives should be integrated into future research. Synthesis and applications. Management of human‐impacted ecosystems can be guided most directly by understanding the response of ecosystem functions to controllable perturbations. In particular, we need to characterize the form of a wide range of perturbation–function relationships and to draw connections between those patterns and the underlying ecological processes. We anticipate that the integrated perspectives will also be helpful for managers to derive practical implications for management from academic literature.